Proteomic characterization of Pseudomonas aeruginosa PAO1 inner membrane. Issue 16 (17th July 2013) - Casabona, Maria G.; Vandenbrouck, Yves; Attree, Ina; Couté, Yohann
<x xml:space="preserve">Abstract</x> Pseudomonas aeruginosa is a Gram‐negative bacterium that can inhabit a wide variety of environments and infect different hosts. Human infections by this microbe are nowadays perceived as a major health problem due notably to its multiresistance. The present data set provides the first description of P. aeruginosa inner membrane proteome. To achieve this, we combined efficient separation of membranes from PAO1 reference strain using discontinuous sucrose gradient centrifugation and MS‐based proteomic analysis. A core list of 991 nonredundant proteins was established and analyzed in terms of trans‐membrane domains, signal peptide, and lipobox sequence prediction. Furthermore, functional insights into membrane‐spanning and membrane‐associated protein complexes have been explored. All mass spectrometry data have been deposited in the ProteomeXchange with identifier PXD000107.